THE EFFECT OF STUDENTS TUTORING, MENTORING AND COUNSELLING PROGRAMME (STUMEC) ON PUPILS’ PERFORMANCE IN INGAWA LOCAL GOVERNMENT AREA OF KANO STATE - Ali, Binta Ado (Sokoto Educational Review, 2020)
Students Tutoring, Mentoring and Counselling programme (STUMEC) is an initiative by United Nation Children’s Fund (UNICEF) aimed at improving girls’ chances in school by reducing drop-out/failure rates through conscious efforts at tutoring, mentoring and counseling learners especially girls at risk. This paper assesses the impact of this programme on pupils’ performances in some selected UNICEF assisted schools in Ingawa L.G.A. by comparing performances of pupils implementing STUMEC and those that are not. Two null hypotheses were tested and significant difference existed in the performances of pupils from schools with STUMEC and those without. It is concluded that STUMEC affect academic performance of pupils positively. Some recommendations were offered such as government to make a policy on implementation of STUMEC at all levels of primary education.